192k views
3 votes
F(x) = (x^2 + x - 2)/(x^2 - 3x - 4)

pls show work! thank you!

F(x) = (x^2 + x - 2)/(x^2 - 3x - 4) pls show work! thank you!-example-1
User Mscrivo
by
4.9k points

1 Answer

5 votes

Answer:

the Domain is x = -1,4

the range is infinite

x and y : x=-2, x=1 y = 1/2

the horizontal y = 1

the vertical x=-1 x=4

Explanation:

X -inter.....When the quotient of expressions equals 0, the numerator has to be 0

x^2+ x-2 / x^2 -3x -4 ===> x^2 +x-2 = 0

Write x as a difference

x^2+2x-2-x-2=0

factor out x from the expression

x(x+2) -x-2=0 ==> x(x+2)-(x+2)=0

factor out x+2 from the expression

(x+2)x(x-1)=0

x+2=0

x-1=0

x=-2

x-1=0

x=-2 x=1

x1 = -2 x2=1

y-inter.... to find y-inter, sub x=0

0^2 + 0-2 / 0^2 -3(0) -4

0-2 / 0^2 -3(0) -4

0-2 / 0-3x0-4

0-2/ 0-0-4

-2/-0-4 ===> -2/-4

reduce the fraction : 1/2

User Sqram
by
4.7k points